Pelatihan Penggunaan Bahasa Inggris Pariwisata (English For Tourism) Bagi Pemuda,Pelaku UMKM dan Aparatur Desa Wisata Rutong, Kota Ambon - Pattipeilohy, Vascolino; Gomies, Stevanus J; Sandanafu, Sally P; Tousalwa, Carla (Journal Of Human And Education (JAHE), 2025)
Community service activities carried out by the PKM team of Ambon State Polytechnic in the Rutong tourist village are based on the needs of village residents for English, especially Tourism English. This PKM aims to provide teaching and motivate the community (youth, MSMEs and village officials) in using English to entertain foreign guests. The training methods used are theory and practice with teaching module materials that have been created by the PKM team. It is expected that from this training, participants will be able and confident in communicating in English with foreign visitors concequently, visitors can understand the explanations of residents regarding Rutong village tourism